Molecular characterization of enteroviruses associated with neurological infections in Spain, 2008. Issue 11 (25th July 2013) - Cabrerizo, M.; Trallero, G.; Echevarría, J.E.; Moreno‐Docón, A.; Pena, M.J.; Pérez‐Ruiz, M.; Avellón, A.; de Ory, F.; ,
Abstract In order to investigate the etiology of viral neurological infections in Spain, a national study was performed in 2008. The results obtained have been published. Enteroviruses were the most frequent cause of the aseptic meningitis and infant febrile syndromes. The present report supplements the previous study with the genotyping of the detected enteroviruses. Typing was by amplification of partial VP1 region and sequencing in 70 (53%) of the 132 available cerebrospinal fluid samples positive for enteroviruses. Twelve different genotypes within the B species were identified. Echovirus 4 was predominant (24%), followed by echovirus 30 (19%), echovirus 9 (17%), and echovirus 6 (14%). In summary, a co‐circulation of several enterovirus types associated with meningitis in children under 15 years old was observed. Although infrequently detected, echovirus 4 was the predominant genotype identified due to an aseptic meningitis outbreak which occurred in the Canary Islands in 2008. J Med. Virol. 85:1975–1977, 2013. © 2013 Wiley Periodicals, Inc.